Comparative line position and line strength analysis of the 𝜈2∕𝜈4 dyad of 12CD4 and 13CD4 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Nikolaeva N. I. Natalya Ivanovna; Merkulova M. A. Maria Andreevna; Morzhikova Yu. B. Yuliya Borisovna; Sydow Ch. Christian; Maul Ch. Christof; Bauerekker (Bauerekker) Z. Kh. Zigurd Khermann (2023, 2023)
Title screen